FOXA2 depletion leads to mucus hypersecretion in canine airways with respiratory diseases. (10th October 2018) - Choi, Woosuk; Yang, Alina X.; Waltenburg, Michelle A.; Choe, Shawn; Steiner, Madeline; Radwan, Ahmed; Lin, Jingjun; Maddox, Carrol W.; Stern, Adam W.; Fredrickson, Richard L.; Lau, Gee W.
Abstract: Because of exposure to environmental pollutants, infectious agents, and genetic predisposition, companion animals develop respiratory illnesses similar to those in humans. Older dogs of smaller breeds develop canine infectious respiratory disease, chronic bronchitis, and chronic obstructive pulmonary disease, with chronic lung infection, airway goblet cell hyperplasia and metaplasia, and mucus hypersecretion. Excessive mucus clogs airways, reduces gas exchanges, disables the mucociliary clearance, and reduces drug penetration. The Forkhead box protein A2 (FOXA2) is a key transcriptional regulator that maintains airway mucus homeostasis. Prior studies have shown that FOXA2 expression is frequently depleted in diseased human airways. Unfortunately, FOXA2 depletion has not been examined in dogs. Our current study indicated that both single bacterial infection by Pseudomonas aeruginosa and Bordetella bronchiseptica and polymicrobial infection by viral/bacterial pathogens depleted FOXA2 in canine airways, resulting in goblet cell hyperplasia and metaplasia and excessive mucus production. Furthermore, P. aeruginosa virulence factor pyocyanin activated the antagonistic STAT6 and epidermal growth factor receptor signalling pathways to inhibit FOXA2. Unravelling the mechanism of FOXA2 inactivation will hasten the development of non‐antibiotic therapeutics to improve mucociliary clearance of pathogens in canine airway.